2021
DOI: 10.1111/jora.12623
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Development in Context: A Decade Review of Neighborhood and Activity Space Research

Abstract: Over the last decade, two lines of inquiry have emerged from earlier investigations of adolescent neighborhood effects. First, researchers began incorporating space‐time geography to study adolescent development within activity spaces or routine activity locations and settings. Second, cultural‐developmental researchers implicated neighborhood settings in cultural development, to capture neighborhood effects on competencies and processes that are salient or normative for minoritized youth. We review the decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 180 publications
(229 reference statements)
1
15
0
Order By: Relevance
“…Additionally, our sensitivity analyses showed that intraindividual changes in neighborhood concentrated poverty were not implicated in the development of externalizing or internalizing symptoms among U.S. Mexican adolescents and did not offer a viable alternative explanation for associations between intraindividual changes in neighborhood white concentration and externalizing symptoms. This is consistent with prior work, which found no association between Latinx and U.S. Mexican adolescents' changes in internalizing and externalizing symptoms in the context of static levels of neighborhood concentrated poverty (Estrada-Mart ınez et al, 2019;Frank et al, 2007;Gonzalez et al, 2011; see also White et al, 2021). Finally, all associations between neighborhood white concentration and symptoms trajectories were the same across boys and girls and across U.S.-and Mexico-born adolescents.…”
Section: Neighborhood White Concentrationsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, our sensitivity analyses showed that intraindividual changes in neighborhood concentrated poverty were not implicated in the development of externalizing or internalizing symptoms among U.S. Mexican adolescents and did not offer a viable alternative explanation for associations between intraindividual changes in neighborhood white concentration and externalizing symptoms. This is consistent with prior work, which found no association between Latinx and U.S. Mexican adolescents' changes in internalizing and externalizing symptoms in the context of static levels of neighborhood concentrated poverty (Estrada-Mart ınez et al, 2019;Frank et al, 2007;Gonzalez et al, 2011; see also White et al, 2021). Finally, all associations between neighborhood white concentration and symptoms trajectories were the same across boys and girls and across U.S.-and Mexico-born adolescents.…”
Section: Neighborhood White Concentrationsupporting
confidence: 90%
“…Evidence gained from this research and derived from predominantly non‐Latinx samples or samples that were heterogeneous on race and ethnicity has often found that neighborhood concentrated poverty was a risk factor for higher internalizing and externalizing spectrum problems (see Chang et al., 2016; Leventhal et al., 2019, for reviews). In research specifically with U.S. Latinx and U.S. Mexican adolescents, however, neighborhood concentrated poverty often fails to predict internalizing and externalizing symptoms (Frank, Cerda, & Rendon, 2007; Gonzales et al., 2011; see also White et al., 2021). One hypothesis, deriving from segmented assimilation perspectives, suggests that lower income Latinx ethnic and immigrant communities have high degrees of social and cultural cohesion that can promote positive development among Latinx adolescents (Burchfield & Silver, 2013).…”
Section: Changes In Internalizing and Externalizing Across Adolescencementioning
confidence: 99%
“…Neighborhood and place characteristics are often studied in relation to Black youth' s behavior, mental health, and academic outcomes. Multiple reviews have examined how neighborhood characteristics, both structural (e.g., demographics such as educational attainment, poverty, and racial/ ethnic composition) and social (e.g., cohesion, trust, belonging), influence youth development (see White et al, 2021). Yet few studies focus on cultural stressors (i.e., discrimination), cultural assets (ERI, ERS), or Black immigrants; we highlight this literature and encourage scholars to take a phenomenological variant of ecological systems theory (Spencer et al, 1997) approach that incorporates neighborhood and how youth make sense of it in relation to their development.…”
Section: Neighborhoodmentioning
confidence: 99%
“…While neighborhood disorder and alcohol outlet density could negatively impact adolescents’ behaviors, some environmental and institutional resources could be associated with positive effects [ 33 ]. In particular, the level of greenness, the density of green spaces, the density of community organizations and walkability could prevent DV through several mechanisms.…”
Section: Contextmentioning
confidence: 99%